Electromagnetic Measurements for Monitoring Molybdenum Contamination in Near-Surface Survey (2015)
We carried out electromagnetic measurements in the vicinity of the near surface molybdenum contamination observed in the “Blue Lagoon” plum located in the north-east of Hungary. The aim of the investigation was to find the origin of the molybdenum pollution, situated in the area, which could be a container or other infrastructure leading to the source of contamination. The field study was conducted in two stages. In the first phase, we gathered electromagnetic data by using GEM-2 type equipment. We derived conductivity and susceptibility maps for each acquired frequency from the electromagnetic data. In the second stage of the field study, GPR data were obtained from 50 MHZ and 450 MHz antennas. In the GPR measurements, we gathered detailed information from GPR depth slices from very shallow depth ranges to deeper parts of the investigated area (from 50cm to 8 m depths). In all results from the measurements executed by the GEM-2 and (50 MHZ and 450 MHz) GPR equipment, there are several clear anomalies are observed in the data for the distribution of molybdenum contamination. Although there are several contaminated zones observed, no clear evidence of the source of contamination was found in the vicinity of the molybdenum pollution peak.   Mediciones Electromagnéticas para Rastrear la Contaminación de Molibdeno en un Estudio de SuperficiesResumenEn este estudio se llevaron a cabo mediciones electromagnéticas en las inmediaciones de un foco de contaminación de molibdeno hallado en el "Blue Lagoon", al noreste de Hungría. El propósito de la investigación fue encontrar el origen de la contaminación de molibdeno, detectada en el área, y que podría ser el contenedor u otra infraestructura que lleve a la fuente de polución. El trabajo de campo se llevó a cabo en dos partes. En la primera fase se reunió la información electromagnética a través del equipo GEM-2. De esta forma se obtuvieron mapas de conductividad y susceptibilidad para cada frecuencia adquirida de la información electromagnética. En la segunda fase del estudio de campo se obtuvieron datos del radar de penetración terrestre (GPR, en inglés) con antenas de 50 y de 450 megahercios (MHZ). En las mediciones GPR se recopiló información detallada de las muestras de penetración en un rango desde la superficie a la profundidad en el área de estudio (desde 50 cm a 8 m de profundidad). En todos los resultados de las medidas hechas con los equipos GEM-2 y GPR se encontraron varias anomalías en la distribución de datos de la contaminación por molibdeno. A pesar de que se observaron varias zonas contaminadas, no hay evidencia clara de la fuente de polución encontrada alrededor del pico de contaminación por molibdeno.